Promoting Intellectual And Physical Development In Elementary Students Through Sports And Games - pcadmin, Jaloliddin AMIRKULOV (Global Scientific Publishing, 2024)
This study aims to support intellectual and physical development in primary school students through sports and games. Sports and games play an important role not only in increasing physical activity, but also in developing students' mental and social skills. The study focuses on developing students' concentration, logical thinking, teamwork and leadership skills through sports and games. As a result, sports and games are used as an effective tool for the comprehensive development of students.
Keywords: Sports; games; intellectual development